Software Business 14th International Conference, ICSOB 2023, Lahti, Finland, November 27-29, 2023, Proceedings - Hyrynsalmi, Sami; Münch, Jürgen; Smolander, Kari; Melegati, Jorge (Lecture Notes in Business Information Processing, 2024)
This open access book constitutes the refereed proceedings of the 23rd International Conference on Software Business, ICSOB 2023, which was held in Lahti, Finland, during November 27-29, 2023. The special theme of ICSOB 2023 was Digital Agility: Mastering Change in Software Business and Digital Services. The 27 full papers and 8 short papers presented in this book were carefully reviewed and selected from 79 submissions. They were organized in topical sections as follows: Requirements; software procurement; platforms, ecosystems and data; artificial intelligence; software startups; software product management; software and business co-development; and emerging digital world. .